THE ROLE OF GENDER EQUALITY AND THE WAYS OF GENERAL AMELIORATION OF THUS FIELD - Ahmadova Maftuna Azimovna (Лучшие интеллектуальные исследования, 2024)
Abstract: Gender equality can be understood as part of the long-term historical struggle for equality and democracy. In this process, gender equality interventions are important tools in enhancing women’s rights and participation, yet this striving for greater gender equality is by no means unproblematic, for example, as demonstrated by LGBTQI movements. There are many arguments for gender equality – feminist transformation, gender justice, gender difference, realization of individual and collective potential, and its fuller use – and many ways of framing gender equality. Within liberal reform feminism, gender equality involves realizing the potential of women and men equally within the current gender order. In resistance feminism, the gender order cannot be made equal through gender balance, as men’s dominance is too strong. Rebellion feminists seek to take apart the gendered social order by multiplying genders or doing away with them. Gender policy operates differentially at organizational and occupational levels, and in public and private sectors, with extremely variable historical contexts. Major supranational bodies, such as the United Nations, the European Union, and the Council of Europe, have been prominent in promotion of gender equality. Various critiques of gender equality are outlined. Future challenges facing gender equality and gender equality policy are noted.